Thermochromic Silks for Temperature Management and Dynamic Textile Displays - Wang, Yang; Ren, Jing; Ye, Chao; Pei, Ying; Ling, Shengjie (Nano-Micro Letters, 2021)
Silks have various advantages compared with synthetic polymer fibers, such as sustainability, mechanical properties, luster, as well as air and humidity permeability. However, the functionalization of silks has not yet been fully developed. Functionalization techniques that retain or even improve the sustainability of silk production are required. To this end, a low-cost, effective, and scalable strategy to produce TCSs by integrating yarn-spinning and continuous dip coating technique is developed herein. TCSs with extremely long length (> 10 km), high mechanical performance (strength of 443.1 MPa, toughness of 56.0 MJ m−3, comparable with natural cocoon silk), and good interfacial bonding were developed. TCSs can be automatically woven into arbitrary fabrics, which feature super-hydrophobicity as well as rapid and programmable thermochromic responses with good cyclic performance: the response speed reached to one second and remained stable after hundreds of tests. Finally, applications of TCS fabrics in temperature management and dynamic textile displays are demonstrated, confirming their application potential in smart textiles, wearable devices, flexible displays, and human–machine interfaces. Moreover, combination of the fabrication and the demonstrated applications is expected to bridge the gap between lab research and industry and accelerate the commercialization of TCSs. Highlights: 1 Wearable and smart textiles are constructed by integrating embroidery technology and 5G cloud communication, showing promising applications in temperature management and real-time dynamic textile displays. 2 Thermochromism is introduced into the natural silk to produce high-performance thermochromic silks (TCSs) through a low cost, sustainable, efficient, and scalable strategy. 3 The interfacial bonding of the continuously produced TCSs is in situ analyzed and improved through pre-solvent treatment and is confirmed using synchrotron Fourier transform infrared microspectroscopy.